Variables affecting the recombinant phytase production from Escherichia coli DH5a - Mohd Ariff, Rafidah; Abd. Manap, Mohd. Yazid; Ideris, Aini; Kassim, Azhar; Farouk, Abd-El Aziem; Meor Hussin, Anis Shobirin (Oriental Scientific Publishing, 2015)
Screening for the important variables is part of the optimization study of enzyme production. It is important indetermining the influential variables that give a significant effect on the enzyme production. Thus, the objective of this study was to determine variables that are effecting the recombinant phytase production from Escherichia coli DH5±. Through the application of the Fractional Factorial Design, the variables of seed age, inoculum level, time of induction, L-arabinose concentration and post-induction time were highly significant for the recombinant phytase production as their p-values were less than 0.05.Thus, minimal changes of this factor mat effect recombinant phytase production from E. coli DH5±.